2000
DOI: 10.1063/1.1330225
|View full text |Cite
|
Sign up to set email alerts
|

Surface effects and high quality factors in ultrathin single-crystal silicon cantilevers

Abstract: Surface effects in ultrathin single-crystal silicon cantilevers of 170 nm thickness, which are optically actuated mainly by the light pressure effect, are investigated under ultrahigh vacuum (UHV) condition. Annealing the cantilevers at 1000 °C for 30 s in UHV results in an over 1 order of magnitude increase of the quality factor (Q factor), up to about 2.5×105 for cantilevers of 30–90 μm in length. The improvement of Q factor was found to be associated with the deoxidization of the surface, as determined by x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(92 citation statements)
references
References 9 publications
3
89
0
Order By: Relevance
“…Among the different mechanisms affecting semiconductor-based NEMS the most important and difficult to avoid are i) clamping losses h L w t The height above the substrate is h. A schematic view of the surface is given, highlighting imperfections like roughness and adsorbates, which dominate dissipation at low temperatures. 33,34 , through the transfer of energy from the resonator mode to acoustic modes at the contacts and beyond to the substrate, ii) thermoelastic damping 35,36,37 and iii) friction processes taking place at the surfaces 38,39,40 . At low temperatures and for decreasing sizes the prevailing mechanism is the last one 6 , as indicated by the linear decrease of the quality factor of flexural modes with decreasing size (see fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different mechanisms affecting semiconductor-based NEMS the most important and difficult to avoid are i) clamping losses h L w t The height above the substrate is h. A schematic view of the surface is given, highlighting imperfections like roughness and adsorbates, which dominate dissipation at low temperatures. 33,34 , through the transfer of energy from the resonator mode to acoustic modes at the contacts and beyond to the substrate, ii) thermoelastic damping 35,36,37 and iii) friction processes taking place at the surfaces 38,39,40 . At low temperatures and for decreasing sizes the prevailing mechanism is the last one 6 , as indicated by the linear decrease of the quality factor of flexural modes with decreasing size (see fig.…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures and for decreasing sizes the prevailing mechanism is the last one 6 , as indicated by the linear decrease of the quality factor of flexural modes with decreasing size (see fig. [2]), or the sharp increase of Q when the resonator is annealed 38,41 . Excitation of adsorbed molecules, movement of lattice defects or configurational rearrangements absorb irreversibly energy from the excited eigenmode and redistribute it among the rest of degrees of freedom of the system.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanical modes possesses highest quality factor up to 3.2 × 10 5 , as shown by the frequency response plot in Figure 3c . Th e high quality factor of the resonator (in vacuum 0.1 mTorr) might be due to the reduced surface loss 24 and clamping loss 25 , through proper Si surface high-temperature annealing treatment processes and the induced tensile stress to the Si fi lm, respectively ( Supplementary Discussion ). Measured standing-wave vibration amplitude 2D mapping pattern of this mode was shown in Figure 3d .…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that submK cooling is feasible with this technique. Optical actuation of cantilevers by light has already been demonstrated [5,6]. In our case, the cantilever functions both as a high-frequency detector and as a high-Q filter.…”
mentioning
confidence: 80%